Preparation method for improving fast charging performance of graphite negative electrode material
Through mechanical force treatment and coating technology on graphite negative electrode materials, the existing materials have been solved inadequate performance in fast charging and energy replenishment, and more efficient lithium embedding capability and charging efficiency are achieved.
Patent Information
- Application Number
- CN202411855669.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
The existing graphite negative electrode materials have insufficient performance in fast charging and energy replenishment, which is difficult to meet the market's demand for efficient charging.
By performing mechanical force on the artificial graphite negative electrode material, local fracture and tear are caused, so that graphite end faces with strong lithium embedded capacity can be regenerated on the basis of the native structure, and combined with the composite technology of solid-phase and liquid-phase coating agent, the positive pressure dynamic medium-temperature carbonization can achieve uniform coating and modification of the new end face.
It significantly improves the rapid lithium embeddedness capability of graphite negative electrode materials, increases the area of lithium embedded end surfaces, improves charging efficiency, and meets the market demand for efficient charging.
Smart Images

Figure CN119683616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphite negative electrode materials for lithium ion batteries, and in particular to a preparation method for improving the fast charging performance of graphite negative electrode materials. Background Art
[0002] Lithium-ion batteries have become a hot topic in the world due to their high energy density, long service life, multiple cycles of charge and discharge, and convenient portability. They are widely used in power vehicles, energy storage base stations, and portable energy storage devices. At present, lithium-ion batteries that have been commercialized on a large scale mainly use carbon materials based on graphite as the negative electrode materials of lithium-ion batteries. However, the commercial use of graphite negative electrode materials in power and digital products has not significantly improved the problem of fast charging and energy replenishment, and has always been an important indicator for terminal consumption in the lithium battery power vehicle market. In recent years, the top domestic power battery manufacturers have joined forces with their material suppliers to invest a large amount of research and development funds each year to study the problem of fast charging and energy replenishment of new energy batteries. In recent years, 3C-4C charging battery products have been installed and applied, but related application products are difficult to fully meet the needs of the terminal market. The products of some domestic leading new energy vehicle companies are in urgent need of battery products with higher energy replenishment efficiency to match; for example, products with 5C-10C charging and energy replenishment efficiency. The charging efficiency of the battery cell is not only related to the battery cell design, but also closely related to the chemical system materials used in the battery cell, such as the graphite negative electrode material that plays the role of the anode in the battery cell. Therefore, the development of graphite negative electrode materials with stronger fast charging capabilities is one of the research focuses for the future development of lithium-ion batteries and an issue that needs to be urgently addressed.
[0003] The mainstream graphite negative electrode material products currently used in the market are mainly obtained by coating the surface of graphite particles with a layer of soft carbon or hard carbon and other carbon-based materials and alloy materials that have a certain improvement in the fast charging effect; however, such methods often have limited effects on the improvement of the fast charging performance of graphite negative electrode materials; because the amount of end faces that can be embedded with lithium in the original structure of graphite is relatively stable, even if a coating layer is coated on the surface of the graphite negative electrode material particles to improve the fast charging performance of the material, it cannot change the end face channel area that has the conditions for lithium embedding in the original structure of the graphite negative electrode material before coating. It still cannot meet the demand for more efficient lithium embedding per unit time.
[0004] It can be seen that the existing methods for improving the fast charging performance of graphite negative electrodes have certain limitations and are difficult to meet the market demand for product charging efficiency.
[0005] Therefore, it is necessary to develop a preparation method for improving the fast charging performance of graphite negative electrode materials, so as to obtain a better method for improving graphite negative electrode materials and overcome the technical difficulties in this technical field. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method for improving the fast charging performance of graphite negative electrode materials in view of the shortcomings of the fast charging performance of graphite negative electrode products produced by the prior art; this method is mainly based on artificial graphite negative electrode materials, through the action of mechanical force, the graphite is partially broken and torn, and then more graphite end faces with lithium insertion ability are regenerated on the basis of the original structure of the graphite negative electrode material, and then compounded by room temperature solid phase and liquid phase coating agents. Through heating and extrusion, the solid phase and liquid coating machine are fully in contact with the graphite negative electrode material particles, and even the coating agent is embedded in the new end faces of the graphite fracture and tear under the action of extrusion force to achieve the purpose of modification. At the same time, in conjunction with positive pressure dynamic medium temperature carbonization, the material is dynamically turned over and moved, and the solid phase coating agent and the liquid phase coating agent are uniformly coated on the original cross section of the graphite negative electrode material, and the coating modification of the new lithium insertion end faces generated by the fracture and tearing of the graphite due to the action of mechanical force is further completed. Through the above method, the area of the lithium-embedded end face of graphite is greatly increased on the basis of the original structure of graphite, and at the same time, combined with positive pressure rolling medium-temperature carbonization, the ability of graphite to quickly embed lithium on the basis of the original structure is significantly improved.
[0007] In order to solve the above technical problems, the technical solution provided by the present invention is: a preparation method for improving the fast charging performance of graphite negative electrode materials, comprising the following steps:
[0008] S1: Select artificial graphite negative electrode material: select primary particle products, secondary particle products or primary particle and secondary particle composite products of artificial graphite negative electrode material with medium particle size D50: 9-18μm, D99: 28-54μm;
[0009] S2: hot kneading the artificial graphite negative electrode material selected in S1 with a carbon-based solid-phase coating agent and a liquid-phase coating agent to obtain kneaded graphite; and pressing the kneaded material into a graphite sheet with a thickness of micrometers by a roller press under heat preservation;
[0010] The ratio of the hot kneaded graphite negative electrode product to the carbon-based solid phase coating agent and the liquid phase coating agent is 82:3:15; the hot kneading temperature is 120°C; the roller pressing material insulation temperature is: 120°C; the kneaded graphite roller pressing sheet thickness is: the D99 value of the selected artificial graphite negative electrode material
[0011] ×(50%~150%) microns;
[0012] S3: Carbonizing the graphite sheet material prepared in S2 by medium-temperature heat treatment under dynamic conditions, in an inert gas atmosphere, and under a positive pressure environment to obtain medium-temperature carbonized graphite;
[0013] The positive pressure medium temperature heat treatment carbonization, the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200℃; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min;
[0014] S4: The medium-temperature carbonized graphite prepared in S3 is depolymerized, screened and impurities removed to obtain a graphite negative electrode material with improved fast charging performance.
[0015] Preferably, the artificial graphite negative electrode material selected in step S1 is a mainstream fast-charging graphite negative electrode material, a high energy density graphite negative electrode material or a long-cycle graphite negative electrode material.
[0016] The advantages of the present invention are: convenient preparation, the prepared graphite negative electrode material is based on the existing mainstream artificial graphite negative electrode material, and the artificial graphite negative electrode material is further mechanically hot kneaded, extruded, and positive pressure rolled carbonized. Then, through this preparation method for improving the fast charging performance of the graphite negative electrode material, the fast charging performance of the graphite negative electrode material is greatly improved on the original basis.
[0017] Compared with the existing technology for improving the fast charging performance of graphite negative electrode materials, the corresponding preparation method for improving the fast charging performance of graphite negative electrode materials of the present invention is based on the original structure of the material. Through the action of mechanical force, the end face with lithium insertion ability is regenerated on the basis of the original structure of the graphite negative electrode material, thereby greatly improving the total area of lithium insertion channels of the graphite negative electrode material particles; at the same time, the solid-phase coating and liquid-phase coating technologies are combined, and the temperature rise curve is formulated through hot positive pressure conditions, combined with the temperature rise weightlessness curves of the solid-phase and liquid-phase coating agents and the fluidity of the solid / liquid coating agents in different temperature zones during the temperature rise process, the graphite negative electrode material is in the positive pressure space and combined with the extrusion force and shear force of the relative movement of the graphite particles. , completing the smooth and uniform carbon-carbon coating of the end face regenerated graphite surface; not only that, the method for improving the fast charging performance of graphite negative electrode materials described in the present invention is due to the combination of solid-phase and liquid coating agents and the dynamic mutual movement of graphite particles during carbonization and heating, plus the softening fluidity of the coating agent during the temperature rise process and the influence of the positive pressure coating environment. The coating agent has a good coating and repair effect on the new end face liquid of the regenerated graphite negative electrode material particles. It should be clear that after the end face of the regenerated graphite particles is coated, the solid-phase and liquid-phase coating agents are evenly covered with residual carbon, which is also an efficient lithium insertion channel; for this reason, the method described in the present invention belongs to the open source of lithium insertion channels on the original structure of graphite negative electrode materials. The residual carbon coating is more uniform and the coating coverage is more comprehensive. For this reason, in the existing coating technology for improving the fast charging performance of graphite negative electrode materials, the method of the present invention has a more significant improvement in the fast charging performance of graphite. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Attached Figure 1 SEM of graphite anode material to select graphite anode material to break and tear under roller pressing, and then regenerate new lithium-inserted end surface
[0019] Attached Figure 2 Illustration of direct carbon coating of the native structure of selected graphite anode materials
[0020] Attached Figure 3 Illustration of carbon coating on the regenerated lithium-intercalated end face of the selected graphite anode material
[0021] Attached Figure 4 This is the interface state of the negative electrode sheet of the embodiment 2.0AH laminated battery after high-rate charge and discharge, and after the battery is disassembled, the interface of the negative electrode sheet of the implementation group is golden yellow after the material rate test of the implementation group of the present invention, the interface is good, and no lithium precipitation phenomenon is found;
[0022] Attached Figure 5 The interface state of the negative electrode sheet of the comparison group after disassembling the battery cell after high-rate charge and discharge of the 2.0AH laminated battery cell and the comparison group; under the same rate and the same test step conditions, after the material rate test of the comparison group, the interface of the negative electrode sheet of the disassembled battery cell of the comparison group appears black, indicating that the lithium precipitation phenomenon is obvious. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the following is a detailed description in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0024] Example 1
[0025] In this embodiment, a preparation method for improving the fast charging performance of graphite negative electrode materials specifically includes:
[0026] S1: Select artificial graphite negative electrode material; the particle structure is secondary particles, the medium particle size D50 is 10-12μm, and D99 is 30-34μm;
[0027] S2: The graphite negative electrode product selected in S1 is mixed with a carbon-based solid-phase coating agent and a liquid-phase coating agent in a ratio of 82:3:15; the mixed material is kneaded to obtain a mixed material at a constant temperature of 120°C; the mixed material is rolled and sheeted under a heat preservation state, and the sheet thickness is 26-28μm to obtain sheeted graphite;
[0028] S3: Carbonizing and coating the pressed graphite obtained in S2 in a positive pressure carbonization furnace to obtain carbonized graphite; wherein the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200°C; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m 3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min. The carbonized graphitized material is depolymerized and the finished product is screened to obtain the graphite negative electrode material with improved fast charging performance in Example 1.
[0029] Example 2
[0030] In this embodiment, a preparation method for improving the fast charging performance of graphite negative electrode materials specifically includes:
[0031] S1: Select artificial graphite negative electrode material; the particle structure is secondary particles, the medium particle size D50 is 16-18μm, and D99 is 50-54μm;
[0032] S2: The graphite negative electrode product selected in S1 is mixed with a carbon-based solid-phase coating agent and a liquid-phase coating agent in a ratio of 82:3:15; the mixed material is kneaded to obtain a mixed material at a constant temperature of 120°C; the mixed material is rolled and sheeted under a heat preservation state, and the sheet thickness is 44-46μm to obtain sheeted graphite;
[0033] S3: Carbonizing and coating the pressed graphite obtained in S2 in a positive pressure carbonization furnace to obtain carbonized graphite; wherein the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200°C; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m 3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min. The carbonized graphitized material is depolymerized and the finished product is screened to obtain the graphite negative electrode material with improved fast charging performance in Example 2.
[0034] Example 3
[0035] In this embodiment, a preparation method for improving the fast charging performance of graphite negative electrode materials specifically includes:
[0036] S1: Select artificial graphite negative electrode material; the particle structure is primary particles, the medium particle size D50 is 9-11μm, and D99 is 28-32μm;
[0037] S2: The graphite negative electrode product selected in S1 is mixed with a carbon-based solid-phase coating agent and a liquid-phase coating agent in a ratio of 82:3:15; the mixed material is kneaded to obtain a mixed material at a constant temperature of 120°C; the mixed material is rolled and sheeted under a heat preservation state, and the sheet thickness is 22-26μm to obtain sheeted graphite;
[0038] S3: Carbonizing and coating the pressed graphite obtained in S2 in a positive pressure carbonization furnace to obtain carbonized graphite; wherein the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200°C; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m 3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min. The graphitized material after carbonization is depolymerized and the finished product is screened to obtain the graphite negative electrode material with improved fast charging performance in Example 3.
[0039] Example 4
[0040] In this embodiment, a preparation method for improving the fast charging performance of graphite negative electrode materials specifically includes:
[0041] S1: Select artificial graphite negative electrode material; the particle structure is primary particles, the medium particle size D50 is 16-18μm, and D99 is 44-48μm;
[0042] S2: The graphite negative electrode product selected in S1 is mixed with a carbon-based solid-phase coating agent and a liquid-phase coating agent in a ratio of 82:3:15; the mixed material is kneaded to obtain a mixed material at a constant temperature of 120°C; the mixed material is rolled and sheeted under a heat preservation state, and the sheet thickness is 36-40μm to obtain sheeted graphite;
[0043] S3: Carbonizing and coating the pressed graphite obtained in S2 in a positive pressure carbonization furnace to obtain carbonized graphite; wherein the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200°C; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m 3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min. The carbonized graphitized material is depolymerized and the finished product is screened to obtain the graphite negative electrode material with improved fast charging performance in Example 4.
[0044] Comparative Example 1
[0045] The method for improving the fast charging performance of the graphite negative electrode material of a lithium-ion battery in this comparative example includes:
[0046] 1-1: Select artificial graphite negative electrode material; the particle structure is secondary particles, the medium particle size D50 is 10-12μm, and D99 is 30-34μm;
[0047] 1-2: The graphite negative electrode product selected from S1 is mixed with the carbon-based solid-phase coating agent and the liquid-phase coating agent in a ratio of 82:3:15; the mixed material is obtained by kneading, and the kneading constant temperature is 120°C;
[0048] 1-3: The kneaded material obtained in S2 is carbonized and coated in a positive pressure carbonization furnace to obtain carbonized graphite; wherein the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200°C; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m 3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min. The graphitized material after carbonization is depolymerized and the finished product is screened to obtain the graphite negative electrode material with improved fast charging performance in Example 1.
[0049] Comparative Example 2
[0050] The method for improving the fast charging performance of the graphite negative electrode material of a lithium-ion battery in this comparative example includes:
[0051] 1-1: Select artificial graphite negative electrode material; the particle structure is primary particles, the medium particle size D50 is 16-18μm, and D99 is 44-48μm;
[0052] 1-2: The graphite negative electrode product selected from S1 is mixed with the carbon-based solid-phase coating agent and the liquid-phase coating agent in a ratio of 82:3:15; the mixed material is obtained by kneading, and the kneading constant temperature is 120°C;
[0053] 1-3: The kneaded material obtained in S2 is carbonized and coated in a positive pressure carbonization furnace to obtain carbonized graphite; wherein the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200°C; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m 3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min. The graphitized material after carbonization is depolymerized and the finished product is screened to obtain the graphite negative electrode material with improved fast charging performance in Example 1.
[0054] The negative electrode materials of Examples 1 to 4 and Comparative Examples 1 to 3 were tested using the following method:
[0055] Malvern laser particle size tester MS3000 was used to test the particle size range and distribution of the material.
[0056] The specific surface area of the material was tested using the Tristar 3000 fully automatic specific surface area and porosity analysis produced by Micromeritics Instruments of the United States.
[0057] Hitachi S4800 scanning electron microscope was used to observe the sample end surface structure, morphology, particle size, etc.
[0058] Use 2.0Ah disc battery cells to test and compare the improvement of graphite fast charging performance, and observe the capacity retention rate at 1C\1C cycle for 500cls; discharge to 3.0V, and charge to 4.2V at constant current and constant voltage at different rates (such as 2C / 3C / 4C / 5C). Disassemble the battery, observe the interface of the negative electrode, take photos in time, and pay attention to the lithium deposition position (pay attention to controlling the temperature and humidity during disassembly).
[0059] The electrochemical rate performance test results of the negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1:
[0060] Table 1
[0061]
[0062]
[0063] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A preparation method for improving the fast charging performance of graphite negative electrode materials, characterized in that: The following steps are involved: S1: Select artificial graphite negative electrode material: select primary particle products, secondary particle products or primary particle and secondary particle composite products of artificial graphite negative electrode material with medium particle size D50: 9-18μm, D99: 28-54μm; S2: hot kneading the artificial graphite negative electrode material selected in S1 with a carbon-based solid-phase coating agent and a liquid-phase coating agent to obtain kneaded graphite; and pressing the kneaded material into a graphite sheet with a thickness of micrometers by a roller press under heat preservation; The ratio of the hot kneaded graphite negative electrode product to the carbon-based solid phase coating agent and the liquid phase coating agent is 82:3:15; the hot kneading temperature is 120°C; the heat preservation temperature of the roller-pressed sheet material is: 120°C; the thickness of the kneaded graphite roller-pressed sheet is: the D99 value of the selected artificial graphite negative electrode material × (50% to 150%) microns; S3: Carbonizing the graphite sheet material prepared in S2 by medium-temperature heat treatment under dynamic conditions, in an inert gas atmosphere, and under a positive pressure environment to obtain medium-temperature carbonized graphite; The positive pressure and medium temperature heat treatment carbonization, the positive pressure of the carbonization furnace is 18-22pa; the carbonization temperature is 1100-1200°C; the carbonization material is turned and stirred at a frequency of 12-16rpm, and the nitrogen flow rate is 2-4m 3 / h, furnace oxygen content 40-60ppm, heating rate: 8-10℃ / min; S4: The medium-temperature carbonized graphite prepared in S3 is depolymerized, screened and impurities removed to obtain a graphite negative electrode material with improved fast charging performance.
2. A method for preparing a graphite negative electrode material for improving fast charging performance according to claim 1, characterized in that: The artificial graphite negative electrode material selected in step S1 is a mainstream fast-charging graphite negative electrode material, a high energy density graphite negative electrode material or a long-cycle graphite negative electrode material.